Multiplexed detection of viral infections using rapid in situ RNA analysis on a chip1. Issue 15 (7th August 2015) - Shaffer, Sydney M.; Joshi, Rohan P.; Chambers, Benjamin S.; Sterken, David; Biaesch, Andrew G.; Gabrieli, David J.; Li, Yang; Feemster, Kristen A.; Hensley, Scott E.; Issadore, David; Raj, Arjun
<x xml:space="preserve">Abstract</x> This paper presents an automated platform for ultra rapid detection of respiratory viruses using RNA FISH.